2016
DOI: 10.1007/s00345-016-1971-7
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of severe incisional hernia after renal transplantation: a retrospective multicentric case–control study on 225 patients

Abstract: We report in this study one of the largest series of patients who had incisional hernia after renal transplantation. Former or active smoking, lymphocele and parietal closure in one single musculo-fascial layer were independent risk factors for incisional hernia following kidney transplant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 28 publications
0
9
0
1
Order By: Relevance
“…1125 patients received sirolimus while 6120 did not. Broggi et al [ 10 ] reported data in the form of an odds ratio rather than raw numbers and these patients have not been included in these numeric descriptors.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1125 patients received sirolimus while 6120 did not. Broggi et al [ 10 ] reported data in the form of an odds ratio rather than raw numbers and these patients have not been included in these numeric descriptors.…”
Section: Resultsmentioning
confidence: 99%
“…Further, closure method with single or multi-fascial closure does not appear to influence the rate of hernia formation. The recently published article by Broggi et al [ 10 ] suggests the single-layered parietal closure increases the odds of hernia formation by 2.89 times. It is unclear, however, how many patients in this group underwent single-layered parietal closure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors associated with incisional hernia were a BMI > 30, age > 50, cadaveric graft and reoperation through the same incision [ 6 ]. Additionally, smoking, lymphocele and partial closure in a single musculofascial layer are other risk factors [ 8 ]. Immunosuppressives such as mTORi (a class of drugs that inhibit the mechanistic Target Of Rapamycine) are known to carry increased risk of incisional hernia formation [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…La predisposición para la formación de una HI, está dada por factores de riesgo sistémicos y locales, ampliamente evaluados en estudios prospectivos y retrospectivos. Dentro de las predisposiciones sistémicas se encuentran el estado nutricional, la ictericia, la diabetes mellitus, la obesidad, el tabaquismo, alteración de las proteínas séricas, edad, género, uso crónico de esteroides y estados de inmunosupresión del paciente [1][2][3][4][5][6][7] . Esta última cobra relevancia, al considerar que estudios previos han mostrado que entre un 2 % y un 10 % de todos los pacientes llevados a una Reparación de Hernia Ventral (RHV), padecen de alguna clase de inmunosupresión (primaria o secundaria) al momento de la intervención quirúrgica.…”
Section: Introductionunclassified